Correlation of Thyroid Stimulating Hormone with Homocysteine and Lipid Profile in Hypothyroidism - Malik, Aqsa; Zaman, Attiya; Izhar, Kausar; Iqbal, Yasir (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To correlate levels of thyroid stimulating hormone with plasma homocysteine and lipid profile in hypothyroid patients METHODOLOGY: This observational study was carried out at Department of biochemistry, Islamic International Medical College, Rawalpindi from March 2016 to Feb 2017. One Hundred Twenty Eight subjects were selected from the medical outpatient department using convenient non probability sampling technique. Age group of 20 to 55 years was the selection criterion whereas any history of diabetes, hypertension, cardiovascular or renal disease was the exclusion criteria. In group I (control) were sixty four healthy volunteers who presented for routine annual medical and physical examination. In group II (patient’s group) were 64 subjects who were diagnosed cases of hypothyroidism on the basis of thyroid stimulating hormone (TSH), free T3 (FT3) and T4 (FT4) levels and clinical features. Estimation of lipid profile and homocysteine levels of both groups was carried out and the data was analyzed using SPSS version 21. Descriptive data were given as mean ± standard deviation (SD). Comparisons between controls and patients groups were performed using independent t-test and p values < 0.05 were considered statistically significant. Pearson correlation coefficients (r) were calculated to quantify the relationship between TSH and other variables. RESULTS: : Group I (control) 82.81% females and 17.18% males. In group II (hypothyroid patients) 87.5% females and 12.5% males. The mean ages of controls and hypothyroid Patients were 33.65±5.98 and 35.20±7.55 years respectively. There was a significant increase in mean Plasma tHcy, total cholesterol, LDL and serum triglycerides in hypothyroid patients than in control group. There was a significant decrease in mean HDL Cholesterol in hypothyroid patients than in control group. TSH was found to be positively correlated to homocysteine, total cholesterol and low density lipoproteins. CONCLUSION: It was found in our study that TSH is positively related to homocysteine, total cholesterol and low density lipoproteins in hypothyroidism rendering the patients to risk of atherosclerosis.